Carryover effect of compelled body weight shift technique to facilitate rehabilitation of individuals with stroke-an assessor blinded randomized controlled trial. - KOVELA RAKESH KRISHNA,; SANGEETHA.G, (International Journal of Pharma and Bio Sciences, 2018)
Stroke in India is very much of rise. It is the commonest cause of death and fourth leading cause of disability worldwide. Stroke is the leading cause of disability in the elderly and a significant source of disability in younger adults. To evaluate the effects of compelled weight shift induced by a lift to the shoe on the stronger (non-paretic) side on the weight bearing in a group of subjects with hemiparesis following stroke.2) To estimate the carryover effect of compelled weight shift in a targeted stroke retraining program. The study was conducted on 30 stroke patients of age between 22 to 82 years randomly divided into experimental and control groups. Shoe lift (innersole) was provided to experimental group but not to the control group. Weight bearing, gait velocity, balance performance and lower extremity functional performance were measured before treatment and after treatment. Follow up was done on 3rd week, 6th week and 9th week from the beginning of the treatment for two months. Weight bearing symmetry Improved in CBWS group compared to Control group, Gait Velocity was decreased in experimental group compared to control group, Balance Performance, lower extremity functional performance were proved to be significantly improved in experimental group than control group. A two-week intervention involving compelled body weight shift technique induced by shoe lift on unaffected side led to the improvement in symmetry of weight bearing and motor recovery of lower extremity in individuals with stroke and this improvement was carried further. Thus a new technique helps to facilitate rehabilitation of individuals with stroke and thus there is a carryover effect of the improvements.